Loads and loads and loads: the influence of prospective load, retrospective load, and ongoing task load in prospective memory - Meier, Beat; Zimmermann, Thomas D. (Frontiers in Human Neuroscience, 2015)
In prospective memory tasks different kinds of load can occur. Adding a prospective memory task can impose a load on ongoing task performance. Adding ongoing task load can affect prospective memory performance. The existence of multiple target events increases prospective load and adding complexity to the to-be-remembered action increases retrospective load. In two experiments, we systematically examined the effects of these different types of load on prospective memory performance. Results showed an effect of prospective load on costs in the ongoing task for categorical targets (Experiment 2), but not for specific targets (Experiment 1). Retrospective load and ongoing task load both affected remembering the retrospective component of the prospective memory task. We suggest that prospective load can enhance costs in the ongoing task due to additional monitoring requirements. Retrospective load and ongoing task load seem to impact the division of resources between the ongoing task and retrieval of the retrospective component, which may affect disengagement from the ongoing task. In general, the results demonstrate that the different types of load affect prospective memory differentially.